Pelaksanaan pepatah petitih adat Minangkabau oleh masyarakat dalam melestarikan alam sekitar - Eri Barlian, (Universiti Kebangsaan Malaysia, 2010)
This article explains the sources of pepatah petitih of Minangkabau custom in using and preserving their environment, and trace the implementation of pepatah petitih by the people who live in Cagar Alam Lembah Harau, West Sumatera. It is found that the sources of pepatah petitih of Minangkabau custom in West Sumatera are the philosophy alam takambang jadi guru (learning from the environment). It proves that environment has a role and great influence on the Minangkabau custom. Unfortunately, the sources of pepatah petitih are no longer used by the society in the way they think and act. As such the concepts that have been tested and incorporated for generations to ensure harmonious relationship between usage and sustainable environment have mostly been discarded by the society. This is due to individual and market needs that can consequently lead to environmental quality degradation and disturb the sustainability of the forest in Cagar Alam Lembah Harau, West Sumatera